Sistem Pendukung Keputusan Pemilihan E-Commerce Terbaik Menggunakan Metode MOOSRA - Zulfi Azhar; Neni Mulyani; Jeperson Hutahaean; Ade Mayhaky (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
Online transactions are transactions that are very popular with many parties today because of the ease of access, ease of transactions and security possessed by each e-commerce, the number of parties who use e-commerce because of the dependence and availability of smartphones and the habits of the current generation on digital age. Every transaction habit contains its own risk to its users, so it is necessary to know the things that must be fulfilled as a user in choosing e-commerce to reduce the risk that will be accepted in the future. This study uses a decision support system logic in analyzing the selection of the best e-commerce using the moosra method. Consider using the method not only based on decisions made by yourself but based on considerations from several previous studies. The results obtained from this study using the moosra method are the highest value of 3.26323 on e-commerce lazada as the best e-commerce.